CF3SO2X (X = Na, Cl) as reagents for trifluoromethylation, trifluoromethylsulfenyl-, -sulfinyl- and -sulfonylation and chlorination. Part 2: Use of CF3SO2Cl - Chachignon, Hélène; Guyon, Hélène; Cahard, Dominique (Beilstein Journal of Organic Chemistry, 2017)
The recent progresses of the application of trifluoromethanesulfonyl chloride, CF3SO2Cl, in the formation of C–CF3, C–SCF3, C–SOCF3, and C–Cl bonds are summarised in this second part of a two-part review published back-to-back on both sodium trifluoromethanesulfinate, CF3SO2Na, (Part 1) and trifluoromethanesulfonyl chloride, CF3SO2Cl (Part 2). There are many reactions in common between these two reagents but it should be noted that CF3SO2Cl reacts under reductive conditions while CF3SO2Na requires oxidative conditions. Electrophilic chlorination is obviously the exclusive preserve of CF3SO2Cl that has been exploited with emphasis in enantioselective chlorination.
Keywords: chlorination; fluorine; sulfur; trifluoromethylation; trifluoromethylsulfenylation; trifluoromethylsufinylation; trifluoromethylsulfonylation